(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The relationship between code-switching, attitude towards English, and students’ academic performance is complex and context-dependent. To address this, the current study employed a concurrent nested mixed-method approach and investigated the relationship between Grade 10 students’ attitudes towards the English language, frequency of code-switching, and academic performance. Sixty students participated in the quantitative portion, and five students took part in a focus group discussion for the qualitative portion. Data were collected using an adapted version of Bernice Anoykes’ questionnaire on Attitudes and Motivation and were analyzed using descriptive statistics and regression analysis. The qualitative responses of the participants were analyzed and organized into categories and themes. Results showed that the students had a moderately favorable attitude towards the English language, a high frequency of code-switching, and were approaching a proficient level in their English academic performance. The study also found that attitudes towards English and the frequency of code-switching significantly influenced their academic performance in English. Remarkably, the participants perceived their attitude towards the English language as a hindrance to learning, expressing apprehension about potential embarrassment and language anxiety. Conversely, they also regarded it as an avenue for career advancement, recognizing its potential for employment opportunities, access to knowledge, and the development of academic literacy. These findings offer important information for teachers and language learners, emphasizing the impact of attitudes towards the English and code-switching on academic achievement. The study suggests that educators promote positive attitudes, authentic language practice, and targeted instruction to enhance language learners’ proficiency and academic success in English.